Меню

УСЛОВИЕ:
Упростите выражение а) 2√3 - √27 + 2√48
б) √8 + 2√18 - √72
в) 2√20 - √35 - 2√12
г) 2√28 - 0,5√24 + 2√7

Преобразуйте выражение, используя формулы сокращенного умножения
а) (2 + √3)(2 - √3)
б) (√6 - 1)(√6 + 1)
в) (√7 - √5)(√7 + 5)
г) (1-√5)^2
д) (√3 - √5)^2
е) (5 - √5)^2 + 5√5


РЕШЕНИЕ:

а) 2√3 - √27 + 2√48
$$ 2 \sqrt{3}- \sqrt{27}+2 \sqrt{48}= 2\sqrt{3}- \sqrt{3^23}+2 \sqrt{4^23}= \sqrt{3}(2-3+8)= 7 \sqrt{3} $$
б) 
√8 + 2√18 - √72
$$ \sqrt{2^22}+2 \sqrt{3^22} - \sqrt{6^22}= \sqrt{2} (2+6-6)=2 \sqrt{2} $$
в) 2√20 - √35 -  2√12
$$ 2 \sqrt{2^25}- \sqrt{5*7}-2 \sqrt{2^23}=4 \sqrt{5}- \sqrt{5*7}-4 \sqrt{3} $$
г) 2√28 - 0,5√24 + 2√7
$$ 2 \sqrt{2^2*7}-0.5 \sqrt{2^2*6}+2 \sqrt{7} =6 \sqrt{7}- \sqrt{6} $$

Преобразуйте выражение, используя формулы сокращенного умножения 
а) (2 + √3)(2 - √3)=4-3=1
б) (√6 - 1)(√6 + 1)=6-1=5
в) (√7 - √5)(√7 + 5)=7-5=2
г) $$ (1 - √5)^2= 1-2 \sqrt{5}+5=6-2 \sqrt{5} $$
д) (√3 - √5)^2=$$ 3-2 \sqrt{3*5}+5=8-2 \sqrt{15} $$
е) (5 - √5)^2 + 5√5
=$$ (25-10 \sqrt{5} +5)+5 \sqrt{5} = 30-5 \sqrt{5} $$






Похожие примеры: